Regulatory B Cells and Their Cytokine Profile in HCV-Related Hepatocellular Carcinoma: Association with Regulatory T Cells and Disease Progression - Hetta, Helal F. (Vaccines (Basel), 2020)
Although regulatory B cells (Bregs) have been proven to play a suppressive role in autoimmune diseases, infections and different tumors, little is known regarding hepatocellular carcinoma (HCC), especially in hepatitis C-related settings. Herein, we analyzed the frequency of circulating Bregs, serum levels of IL-10, IL-35 and B-cell activating factor (BAFF) and investigated their association with regulatory T cells (Tregs) and disease progression in HCV-related HCC. For comparative purposes, four groups were enrolled; chronic HCV (CHC group, n = 35), HCV-related liver cirrhosis (HCV-LC group, n = 35), HCV-related HCC (HCV-HCC group, n = 60) and an apparently healthy control (Control-group, n = 20). HCC diagnosis and staging were in concordance with the Barcelona Clinic Liver Cancer (BCLC) staging system. Analysis of the percentage of Breg cells and peripheral lymphocyte subsets (Treg) was performed by flow cytometry. Serum cytokine levels of IL-10, IL-35 and B-cell activating factor (BAFF) were measured by ELISA. The frequency of Bregs was significantly higher in the HCV-HCC group compared to the other groups and controls. A significant increase was noted in late-HCC versus those in the early stages. The frequency of Bregs was positively correlated with Tregs, serum IL-10, IL-35 and BAFF. In conclusion, Peripheral Bregs were positively correlated with the frequency of Tregs, IL-10, IL-35 and BAFF, and may be associated with HCV-related HCC progression.